KARAKTERISTIK SENSORIS DAN TINGKAT KESUKAAN PADA ISIAN SAMOSA IKAN NILA DAN KACANG MERAH DENGAN PENAMBAHAN DAUN SEMANGGI - Gabriella Regine Widya Swastika; Any Sutiadiningsih; Lilis Sulandari; Ila Huda Puspita (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the interaction of the proportion of nile tilapia and red beans with the addition of clover leaves on the sensory characteristics and the level of preference for nilanggi samosa filling products. The research method is an experiment with a factorial design using and data analysis using the ANOVA - two ways test and Duncan test. The results of this study indicate that there is a significant effect of the interaction for the proportion of nile tilapia and red beans with the addition of clover on the sensory attributes of samosa fillings including color, flavor, taste, texture, and level of preference. The best treatment was found in the proportion of 80% nile tilapia, 20% red beans and 10% clover leaf. The panelist prefer this proportion over the other proportion. As a result, this combination has a good chance of being well received with future consumers.